Karakteristik Kimia dan Sensori Permen Jelly Kopi Robusta (Coffea canephora P.) dengan Proporsi Sukrosa dan Isomalt - Arista, Gita Martya; Hapsari, Distya Riski; Nurlaela, Raden Siti (Jurnal Ilmiah Pangan Halal, 2023)
Jelly candy is a type of non-crystalline candy that is transparent/clear and has a certain degree of chewiness. Robusta coffee has a high content of caffeine, ferulic acid, chlorogenic acid and caffeic acid which are useful as antioxidants. Isomalt is an artificial sweetener that can partially replace sucrose because it has similar properties to sucrose. This study aims to determine the effect of the proportion of sucrose and isomalt on the chemical and sensory characteristics of robusta coffee jelly candy and find the selected jelly candy formulation. This study used a completely randomized design (CRD) with one factor, namely the ratio of sucrose and isomalt (100%: 0%), (90%: 10%), (80%: 20%), and (70%: 30%). Product analysis included chemical analysis of moisture content, ash content, reducing sugar content, sucrose content and sensory and hedonic quality tests. Selected treatments were then tested for antioxidant activity. Data analysis used was Analysis of Variance (ANOVA) with Duncan's further test at 95% confidence interval. The ratio of sucrose and isomalt affects the water content, reducing sugar content, sucrose content, as well as the sensory quality of color, sweetness and bitterness. The results showed that the selected formulation of robusta coffee jelly candy has a texture sensory quality towards chewy, dark brown in color, has an aroma towards typical coffee, has a taste towards sweetness and towards not bitter and in the hedonic test parameters of texture, color, aroma, sweetness, bitter taste and overall which leads to liking, has a moisture content of 25.77%, ash content of 1.84%, reduced sugar content of 11.68%, sucrose content of 34.45% and antioxidant activity of 74.53%. Keywords: robusta coffee, jelly candy, sucrose, isomalt.